2021
DOI: 10.1111/gcb.15724
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in terrestrial ecosystems: Moving beyond the state of the art to minimize the risk of ecological surprise

Abstract: Microplastic (plastic particles measuring <5mm) pollution is ubiquitous. Unlike in other well‐studied ecosystems, for example, marine and freshwater environments, microplastics in terrestrial systems are relatively understudied. Their potential impacts on terrestrial environments, in particular the risk of causing ecological surprise, must be better understood and quantified. Ecological surprise occurs when ecosystem behavior deviates radically from expectations and generally has negative consequences for ecos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 168 publications
0
61
0
Order By: Relevance
“…On the other hand, some studies have shown the terrestrial system as a bigger reservoir for plastic accumulation as opposed to the aquatic system (Blasing & Amelung, 2018; Hurley & Nizzetto, 2018), and thus it is suggested that the terrestrial system can also act as a major sink of microplastics (Baho et al, 2021; Boots et al, 2019; David et al, 2018). About 79% of the plastic waste generated worldwide is disposed in landfills, which again indicates that soil can serve as a large sink for the accumulation of microplastics (Guo et al, 2020).…”
Section: Source and Occurrence Of Micro/nanoplastics In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some studies have shown the terrestrial system as a bigger reservoir for plastic accumulation as opposed to the aquatic system (Blasing & Amelung, 2018; Hurley & Nizzetto, 2018), and thus it is suggested that the terrestrial system can also act as a major sink of microplastics (Baho et al, 2021; Boots et al, 2019; David et al, 2018). About 79% of the plastic waste generated worldwide is disposed in landfills, which again indicates that soil can serve as a large sink for the accumulation of microplastics (Guo et al, 2020).…”
Section: Source and Occurrence Of Micro/nanoplastics In Soilmentioning
confidence: 99%
“…In this regard, it is worth mentioning that many studies have been done under environmentally unrealistic conditions which may be an obstacle to the understanding of their ecological relevance. Baho et al (2021) in a review study showed that many studies measuring toxicities of microplastics in plants have used microplastic concentrations with a range from 0.001% to 2% (w/w). As discussed in this review (Table 1) that different studies measuring the abundance of microplastics in soils have expressed concentrations as: numbers of items/unit weight of soil or number of particles per/unit weight of soil.…”
Section: Micro/nanoplastic Induced Toxicities In Plantsmentioning
confidence: 99%
“…For the University of Reading, the most recent document is focused on productivity, biodiversity trade-offs, and farm income in agroforestry versus an arable system and concluded how a diversified farming system could improve farm income, but support from grants would reduce the initial negative cash flow [ 34 ]. For Sveriges lantbruksuniversitet, the most recent document is a review by Baho et al [ 35 ] on microplastics in terrestrial ecosystems by moving beyond the state-of-the-art to minimize the risk of ecological surprise.…”
Section: Ecosystem Services Pollinators and Biodiversitymentioning
confidence: 99%
“…They were first reported in the Sargasso Sea (Carpenter and Smith, 1972) but it was not until much later that the issue began to attract widespread scientific and popular attention (Thompson et al, 2004). Much of the early focus was on marine systems, but more recently, attention has expanded to include freshwater (Wagner et al, 2014;Eerkes-Medrano et al, 2015;de Sá et al, 2018;Li et al, 2018) and terrestrial environments (Huerta Lwanga et al, 2016;de Souza Machado et al, 2018;Rillig and Lehmann, 2020;Baho et al, 2021). Microplastics are ubiquitous in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial MPs originate from multiple sources including atmospheric deposition (Allen et al, 2019;Klein and Fischer, 2019), leaching from landfills (He et al, 2019), tire wear (Knight et al, 2020), breakdown of agricultural mulch (Huang et al, 2020;Zhang et al, 2020) and application of sewage sludge to agricultural land (Nizzetto et al, 2016a,b;Crossman et al, 2020). Despite multiple lines of evidence suggesting that terrestrial ecosystems are major MPs sinks, microplastic research in the terrestrial environment is still at an early stage (see, e.g., Baho et al, 2021 for a recent review).…”
Section: Introductionmentioning
confidence: 99%